Incidence and remission of aeroallergen sensitization in adults in Northern Finland : 15 years longitudinal study - Haarala, Anna Karoliina; Sinikumpu, Suvi-Päivikki; Vaaramo, Eeva; Jokelainen, Jari; Timonen, Markku; Auvinen, Juha; Pekkanen, Juha; Lampi, Jussi; Huilaja, Laura (Scientific Reports, 2021)
Studies on the longitudinal changes in sensitization to aeroallergens in adult populations are sparse. The aim was to evaluate changes in sensitization to aeroallergens [birch, timothy, cat and house dust mite (HDM)] in an unselected adult population aged from 31 to 46 years. Data were gathered from a cohort of adults (Northern Finland Birth Cohort 1966) who had been skin prick tested (SPT) with birch, timothy, cat and HDM allergens at the age of 31 years and at age 46 (n=5484 and 5373 respectively). Data from both time points were available for 3409 participants, who made up the cohort of the longitudinal study. The overall prevalence of sensitization to any of the selected allergens was 30.3% (n=1661) in 31-year-olds and 30.7% (n=1649) in 46-year-olds. In general, men were more sensitized (P Peer reviewed